Konsep Diri Dalam Menghadapi Quarter Life Crisis - Uti Lestari; Luluk Masluchah; Wardatul Mufidah (IDEA: Jurnal Psikologi, 2022)
This study aims to determine the influence of self-concept in facing the quarter life crisis in students. The hypothesis proposed is the influence of self-concept in the face of quarter life crisis in students. The research methodology used is quantitative research.The subjects of this study were 80 students between 19 and 29 years old in the city of Jombang using random sampling on purpose.The research instruments used in this study are the self-concept scale and the quarter life crisis scale. The data analysis used in this study was the correlation of moments produced through the SPSS (Statistical Package For The Social Sciences) program.Hypothesis Test obtained the correlation coefficient rxy = -0.416 with a significant 0.000 (p<0.01). This shows that there is a very significant negative correlation between self-concept and quarter life crisis, that is, the higher the self-concept, the individual does not experience a cquarter life crisis, so the hypothesis that is addressed .